Production enhancement and chemical characterization of pyocyanin pigment extracted from Pseudomonas aeruginosa - Nubgan, Amer; Lutfi, Khamael (Iraqi Journal of Science, 2026)
Pyocyanin is a blue-greenish phenazine pigment produced by certain strains of Pseudomonas aeruginosa. This secondary product pigment is revealed to have antibacterial, anticancer, antiparasitic, antioxidant, and antibiofilm formation activity. This study investigates the effects of organic solvents, such as toluene, surfactants, and particularly triton X-100, on pyocyanin synthesis in the presence of glycerol. Moreover, the pyocyanin pigment was chemically characterised using Fourie Transform Infra-Red spectroscopy (FT-IR). The results showed the highest yield of pyocyanin was produced when glycerol 1% was the only carbon source used in the growth medium (nutrient broth). The production of pyocyanin went up to 31.1 mg/L and 13.1 mg/L when either 0.2% toluene or 0.3% triton X-100 was added to the nutrient broth along with 1% glycerol. This was compared to the control level of 6.2 mg/L. FT-IR analysis revealed that pyocyanin had a hydroxyl group (O-H), an aromatic hydrocarbon ring (C-H), aliphatic saturated hydrocarbon chains (CH, CH2, CH3), and a C=N bond. It seems that adding glycerol-toluene to the nutrient broth medium can help P. aeruginosa make more extracellular yields, such as pyocyanin. Furthermore, FT-IR analysis showed that pyocyanin is biologically safe (has no biological toxic chemical compounds), and these findings confirmed that pyocyanin could be widely used in applications such as in the therapeutic, medication, nutrition, fabric, bio-control, nanotechnology, and physicochemical industries.